Scaevola rialagartensis (Goodeniaceae), a new species from coastal sand dunes of Rio Lagartos, Yucatan, Mexico - Castillo-Campos, Gonzalo; García-Franco, José G.; Martínez, M. Luisa (Phytotaxa, 2019)
The new species, Scaevola rialagartensis Cast.-Campos is described and illustrated from coastal shrubland and vegetation bordering mangroves in Rio Lagartos, Yucatan, southeastern Mexico, where it is considered endemic. The new species is similar to S. plumieri, S. taccada and S. wrightii, all of which grow in similar environments, but can be differentiated from these in the size of shrubs, shape of axes, and nerves along leaves.